(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
Lifestyle changes have made coffee not just a daily beverage, but a part of lifestyle, leading to the emergence of many new coffee shops and increasing competition. This study aims to analyze the impact of brand image, service quality, and digital promotion on consumer purchase intention at Senga Kopi in Denpasar City. The population in this study is not known with certainty or is infinitive. The number of sample members determined was 150 people using the stratified random sampling method. Hypothesis testing was carried out using multiple linear regression analysis techniques. The results of the analysis proved that partially and simultaneously it can be proven that brand image, service, and digital promotion have a significant effect on consumer purchasing interest. The suggestions given are to increase physical comfort and build a community in coffee shops, optimize the number of staff, operational efficiency, and provide training to employees, and update content and be more responsive on social media.